THE ASSOCIATION BETWEEN COMMUNITY HEALTH CENTER WORKERS AND THEIR PREPAREDNESS TO ANTICIPATE FOR COVID-19 AT WORK - Afaf, Khansa Salsabila; Denny, Hanifa Maher; Wahyuni, Ida (Journal of Public Health Research and Community Health Development, 2022)
ABSTRACT Background: The Central Java Response COVID-19 website shows, Semarang City has the highest COVID-19 cases in Central Java. The coverage area of Rowosari Community Health Center (CHC) has experienced many COVID-19 cases compared to other areas in Semarang City. Meanwhile, the Srondol CHC has shown a rapid decline in COVID-19 cases. Subsequently, the COVID-19 cases in Krobokan CHC have been recorded as low numbers compared to other CHCs in Semarang City. Purpose: The purpose of this study was to analyze the association between the CHC workers' behavior (knowledge, attitude, practice) and the readiness in anticipation of COVID-19 at work. Methods: This study was a quantitative analytic with the google form instrument in collecting the primary data. Meanwhile, secondary data obtained from CHCs, Central Java provincial government, and Semarang City Government were added to enrich the study. The investigators invited 135 persons from the CHC workers. However, only 97 respondents filled the instrument. Results: The majority of respondents were female with a good knowledge of 57 people (58.8%). Respondents with a good attitude were 57 people (58.8%), good practices were 87 people (89.7%), and informed readiness were 88 people (90.7%). There is a significant relationship between knowledge (p-value: 0.002; α: 0.05), attitude (p-value: 0.012; α: 0.05), and practice (p-value: 0.028; α: 0.05) and the readiness of health center officers in anticipation of COVID-19 at work. ABSTRAK Latar Belakang: Merujuk data pada portal Jateng Tanggap COVID-19, Kota Semarang adalah kota yang mempunyai kasus COVID-19 tertinggi di Jawa Tengah. Dari hasil pantauan data COVID-19 maka daerah sekitar puskesmas Rowosari pernah menjadi wilayah dengan kasus tertinggi di Kota Semarang. Sedangkan wilayah kerja puskesmas Srondol menunjukkan penurunan kasus COVID-19 secara cepat. Wilayah kerja Puskesmas Krobokan dipilih karena kasus COVID-19 tergolong rendah di banding wilayah kerja Puskesmas lainnya. Tujuan: Tujuan penelitian ini untuk mengetahui kesiapan dari petugas Puskesmas dalam antisipasi COVID-19 di wilayah kerja masing masing. Metode: Penelitian ini merupakan penelitian kuantitatif analitik. Instrumen yang digunakan dalam penelitian berbentuk googleform untuk pengumpulan data primer. Sedangkan data sekunder diperoleh dari Puskesmas, pemerintah provinsi Jawa Tengah dan Pemerintah Kota Semarang. Jumlah populasi pada penelitian adalah 135 orang pegawai Puskesmas, namun yang bersedia menjadi responden penelitian hanya 97 orang.  Hasil: Dari 97 responden, mayoritas responden adalah perempuan, responden yang mempunyai pengetahuan baik (58,8%), responden dengan sikap baik (58,8%), praktik yang baik (89,7%) dan siap dalam antisipasi COVID-19 sebanyak (90,7%). Ada hubungan secara signifikan antara pengetahuan (p-value: 0,002; α: 0,05), sikap (p-value: 0,012; α: 0,05), dan praktik (p-value: 0,028; α: 0,05) dengan kesiapan petugas Puskesmas dalam antisipasi COVID-19 di Puskesmas Kota Semarang.